2007
DOI: 10.1037/1931-3918.1.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Professional interests and career aspirations of graduate students in professional psychology: An exploratory survey.

Abstract: Graduate students in American professional psychology programs (N ϭ 498) were surveyed to examine differences between specialty area (clinical vs. counseling), degree type (PhD vs. PsyD), and gender with respect to demographics, training models, theoretical orientations, career aspirations and reasons for choices, research productivity, and expected salaries. Clinical and counseling students differed with respect to training models, theoretical orientations, career aspirations, and expected salaries, whereas P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 15 publications
3
32
1
Order By: Relevance
“…When comparing psychology students with students from other courses, a study developed by Leong, Zachar, Conant, & Tolliver (2007) showed that psychology students were more active and enthusiastic entrepreneurs than geography students (higher openness scores) and more inhibited than physical education students (lower extraversion scores). Other authors argued that different forms of cognition that characterize psychology students, namely creativity, appear to be directly linked to innovation and the search for new solutions (e.g., Cassin et al, 2007;Jones & Allen, 2012;Wicherts & Vorst, 2010). Wicherts & Vorst (2010) suggested that the interests, personality, and cognitive abilities of individuals vary systematically between the various specialty degrees in psychology.…”
Section: Interests In Career Areas Of Psychologymentioning
confidence: 98%
See 3 more Smart Citations
“…When comparing psychology students with students from other courses, a study developed by Leong, Zachar, Conant, & Tolliver (2007) showed that psychology students were more active and enthusiastic entrepreneurs than geography students (higher openness scores) and more inhibited than physical education students (lower extraversion scores). Other authors argued that different forms of cognition that characterize psychology students, namely creativity, appear to be directly linked to innovation and the search for new solutions (e.g., Cassin et al, 2007;Jones & Allen, 2012;Wicherts & Vorst, 2010). Wicherts & Vorst (2010) suggested that the interests, personality, and cognitive abilities of individuals vary systematically between the various specialty degrees in psychology.…”
Section: Interests In Career Areas Of Psychologymentioning
confidence: 98%
“…The questions evaluating interest were based on a review of the literature (e.g., Armstrong, Allison, & Rounds, 2008;Cassin et al, 2007;Rodrigues, Ferreira, & Bártolo-Ribeiro, 2013). The development of the questionnaire began by defining the constructs that were distributed over the three dimensions that are important in European psychology: clinical psychology, I-O psychology, and educational psychology.…”
Section: Development Of the Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…Of primary relevance to the current study is a consistent difference in theoretical orientation. Both students and faculty at PsyD programs are more likely to endorse utilizing a psychodynamic orientation, while students and faculty at PhD programs are more likely to endorse utilizing a cognitivebehavioral orientation [23,24] . This being the case, it would be useful to consider doctoral level training degrees as another potential variable that could affect diagnostic preferences.…”
Section: Why Theoretical Orientation Mattersmentioning
confidence: 99%